Tumour necrosis factor alpha gene (TNF-alpha)-376 polymorphism in Hungarian patients with primary progressive multiple sclerosis - Losonczi Erika (JOURNAL OF NEUROIMMUNOLOGY, 2009)
Tumour necrosis factor alpha (TNF-alpha) is associated with clinical activity in relapsing-remitting multiple sclerosis (RRMS) and the development of progressive disease. Our aim was to investigate the TNF-alpha -376 polymorphism in primary progressive MS (PPMS) patients. Polymerase chain reaction and restriction fragment length polymorphism were carried out on 45 PPMS patients, 45 age and sex-matched RRMS patients and 45 healthy controls (HC). The GG genotype and the guanine allele (G) were detected significantly more often in the PPMS group as compared with the HC group (p=0.027; p=0.032). The G allele may be one of the factors responsible for progression in PPMS.